An improved wave equation of fractured-porous media for predicting reservoir permeability - Zhao, Wanjin; Sun, Weitao; Gao, Jianhu; He, Run (Frontiers in Earth Science, 2023)
The wave characteristics of fractured-porous media can be utilized for permeability identification; however, further research is necessary to enhance the accuracy of this identification. A novel wave equation for fractured-porous media is formulated, and theoretical analysis suggests its effectiveness in accurately identifying reservoir permeability. The proposed methodology establishes a wave equation for fractured-porous media using the volume averaging method and employs finite difference method on staggered grids to calculate wave field dispersion and attenuation, exploring the influence of fracture network structure and confining pressure on the solution of the wave equation. By analyzing the wave equation under various aspect ratios and confining pressure of fractures, it is observed that these factors significantly affect velocity and attenuation, providing valuable insights into seismic response in fractured-porous media. Furthermore, the research findings reveal promising potential in utilizing the new wave equations specific to fractured-porous media for permeability identification purposes. By constructing a three-dimensional fractured-porous network model, the wave equation for permeability identification can examine the correlation between the parameters of the equation and permeability, and establishes an association between fracture parameters and permeability, paving the way for a novel approach to permeability identification.